PENGENALAN PEMASARAN DIGITAL PADA UMKM VEZARA DI PGC, CILILITAN JAKARTA TIMUR - Yusbardini, Yusbardini (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
Digital marketing is promotional activities and market search through online digital media by utilizing various means such as social networks. Cyberspace is now no longer only able to connect people with devices, but also people with other people throughout the world. It is hoped that the existence of MSMEs will be able to stimulate the economy amidst the current economic slowdown. The use of digital technology-based marketing concepts (digital marketing) gives hope for MSMEs to develop into economic powerhouses. MSME players collaborate on promotional media and digital-based distribution media to gain maximum profits. Currently, almost all MSME businesses or even restaurants and fast food businesses use digital marketing-based promotional media and distribution media. The aim of this PKM is to provide enlightenment for the progress of MSMEs in the field of marketing by utilizing social media as a means to increase sales